2018
DOI: 10.1158/0008-5472.can-17-3592
|View full text |Cite
|
Sign up to set email alerts
|

MIR142 Loss-of-Function Mutations Derepress ASH1L to Increase HOXA Gene Expression and Promote Leukemogenesis

Abstract: Point mutations in the seed sequence of miR-142-3p are present in a subset of acute myelogenous leukemia (AML) and in several subtypes of B-cell lymphoma. Here, we show that mutations associated with AML result both in loss of miR-142-3p function and in decreased miR-142-5p expression. loss altered the hematopoietic differentiation of multipotent hematopoietic progenitors, enhancing their myeloid potential while suppressing their lymphoid potential. During hematopoietic maturation, loss of increased ASH1L prot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 49 publications
5
63
0
1
Order By: Relevance
“…As there is no list of previously defined miRNA driver genes, we could not formally validate our approach; however, among the top-scored overmutated miRNA genes, we identified hsa-miR-142, which is the only miRNA gene in which mutations were identified in several hematologic neoplasms in several studies [49][50][51][52][53]56,57 , and their cancer relevance was functionally confirmed 27 . Our analysis confirmed the recurrence of hsa-miR-142 mutations in hematologic neoplasms, i.e., LAML, DLBC, and also the newly identified mutation in the Burkitt lymphoma Raji cell line, but also showed mutations in several solid tumors, i.e., UCEC, BLCA, GBM, and BRCA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As there is no list of previously defined miRNA driver genes, we could not formally validate our approach; however, among the top-scored overmutated miRNA genes, we identified hsa-miR-142, which is the only miRNA gene in which mutations were identified in several hematologic neoplasms in several studies [49][50][51][52][53]56,57 , and their cancer relevance was functionally confirmed 27 . Our analysis confirmed the recurrence of hsa-miR-142 mutations in hematologic neoplasms, i.e., LAML, DLBC, and also the newly identified mutation in the Burkitt lymphoma Raji cell line, but also showed mutations in several solid tumors, i.e., UCEC, BLCA, GBM, and BRCA.…”
Section: Discussionmentioning
confidence: 99%
“…This result may suggest that the miRNA hairpin precursor is quite a fragile structure, and therefore, almost any mutation may be deleterious for the gene, either by disturbing the structure of the precursor or by disruption of the seed sequence. A recent functional study of two seed mutations, i.e., chr17:58331264T>C[-] and chr17:58331261C>G[-], showed that even though the mutations are located in miR-142-3p, they result in a decrease in both miR-142-3p and miR-142-5p levels and reverse the miR-5p:3p ratio (in favor of miR-3p) 27 . The functional consequences of the mutations are (i) aberration of hematopoietic differentiation, enhancing the myeloid and suppressing the lymphoid potential of hematopoietic progenitors, and (ii) inefficient repression of ASH1L, resulting in increased levels of HOXA9 and A10 (positively regulated by ASH1L) and ultimately leukemic transformation 27 .…”
Section: Hsa-mir-142mentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study indicated that miR-142-5p functioned to suppress cell migration by targeting VCAM-1 in bone marrow-derived mesenchymal stem cells [40]. Trisaal et al showed that loss-of-function the in miR-142 gene resulted in the increase in HOXA gene (a key gene for maintaining stemness in hematopoietic stem cells) and promoted leukemogenesis [41]. Together, the results from others and this study have provided evidence for the role of miR-142-5p as a tumor suppressor, while the decreased level of miR-142-5p was linked to the EMT and stemness of ESCC.…”
Section: Discussionmentioning
confidence: 99%